Level of Analysis of Factors Contributing to the High Unemployment Rate in Madiun Regency - Oktavia Fauzaturroisiyah; Riko Setya Wijaya (International Journal of Economics, Business and Innovation Research, 2024)
The crucial problems in Indonesia include several things, one of which is unemployment. Various efforts have been made by the Indonesian government to overcome the problem of unemployment. Regarding the condition of the population, the average length of schooling, minimum wage, and GDP in Madium Regency, it is necessary to conduct an impact analysis to see factors that can increase open unemployment in Madiun Regency. The approach taken by the researcher utilizes a quantitative approach, by applying the multiple linear regression analysis method through the ordinary least square. The data used is secondary data, namely data on the Open Unemployment Rate, Number of Population, Average Length of Schooling, Minimum Wage, and GDP during the 2008-2022 period. The results of this study are that the number of population has a significant negative effect on open unemployment in Madiun Regency, the average length of schooling has a significant positive effect on open unemployment in Madiun Regency, the minimum wage has no significant effect on open unemployment in Madiun Regency, and the Gross Regional Domestic Product has a significant positive effect on open unemployment in Madiun Regency. With these results, the Government is expected to create policies that can influence efforts to reduce budgeting in Madiun Regency.